Effect of Spiral Split Ring Resonator (S-SRR)structure on Truncated Pyramidal Microwave Absorber Design - Nornikman, H; Ahmad, B. H.; Othman, A.R; Kamarudin, M. R.; Abdul Aziz, M. Z. A. (2012)
This paper discusses on the effect of the spiral split ring resonator on the truncated pyramidal microwave absorber. Split ring resonator (SRR) structure can potentially be incorporated onto the truncated pyramidal microwave absorber to increase the reflection loss performance. There are many ways to increase the pyramidal microwave absorber performance. The ways are focusing the new hybrid shapes, using high carbon material, and adding the left handed material structure on the pyramid microwave absorber. Left handed material or metamaterial is an artificial material that does not exist in the real nature like FR4, Taconic, Rogers or RT Duriod.There are many types of left handed material that had been used by several researchers such as split ring resonator (SRR), and photonic band gap (PBG), electromagnetic band gap (EBG) and artificial magnetic conductor (AMC). In this research, spiral split ring resonator (S-SRR) is used to increase the microwave absorber performance. It has the potential to increase the reflection loss or 811 results of the microwave absorber at the several frequencies.